Estágios de mudança de comportamento e barreiras percebidas para prática de atividade física em idosos - Dornelles, Nicanor da Silveira (2017)
Aging in Brazil has been increasingly analyzed in physical activity and health studies. Despite all the recommendations and even the concepts of a healthy lifestyle, physical inactivity in the elderly is still a problem in the developing countries and the reasons for non-adherence to an active lifestyle have been studied around the world. The purpose of this study was to analyze the prevalence of stages of behavior change (SBC) and perceived barriers (PB) to physical activity (PA) in elderly of Santa Maria-RS, Brazil. Two hundred and two participants from three neighborhoods of different socioeconomic levels were evaluated. For perceived individual barriers, the questionnaire proposed by Reichert et al. (2007) was used and the SBC was assessed using the questionnaire proposed by Prochaska and Marcus (1994). Results were analyzed by descriptive statistics, chi-square test for the comparisons between categorical variables and for the continuous variables; 1-way ANOVA and Kruskal-Wallis test were used, followed by the Bonferroni post-hoc test. In the lower socioeconomic neighborhood the most cited stages were contemplation (48.15%) and pre-contemplation (27.78%), which are typical of sedentary elderly. In the medium socioeconomic neighborhood, the stages that appeared the most were contemplation (38.78%) and maintenance (32.36%), which are typical stages of sedentary and active elderly, respectively. In the neighborhood of high socioeconomic level the most cited stages were also contemplation (39.62%) and maintenance (26.42%). The most reported PB were "having some injury or disease that interferes with the practice of physical activity" (59.26%) and "laziness and fatigue to practice physical activity" (46.30%) in the lower socioeconomic neighborhood, followed by "lack of company" (46.94%) in the neighborhood of medium socioeconomic level. The barriers "to have some injury or illness that disrupts the practice of physical activity (p=0.023) and "lack of money hinders physical activity" (p=0.020) showed a statistically significant difference between the neighborhoods. The findings of this study showed the impact that the barrier perception exerts on the practice of PA, showing that the higher the number of PB by the elderly, the lower tends to be their PAL. Professionals working with this population should be aware of the possibilities of interventions and planning that reduce or minimize the negative effect of PB on the elderly PAL.